Characterization and Functional Analysis of Toll Receptor Genes during Antibacterial Immunity in the Green Peach Aphid Myzus persicae (Sulzer) - Li He; Chao Zhang; Hong Yang; Bo Ding; Han-Zhi Yang; Sen-Wen Zhang (Insects, 2023)
The insect Toll receptor is one of the key members of the Toll signaling pathway, which plays an indispensable role in insect resistance to pathogen infection. Herein, we cloned and characterized five Toll receptor genes from Myzus persicae (Sulzer), which were found to be highly expressed in the first-instar nymphs and adults (both wingless and winged) at different developmental stages. Expressions of MpToll genes were highest in the head, followed by the epidermis. High transcription levels were also found in embryos. Expressions of these genes showed different degrees of positive responses to infection by Escherichia coli and Staphylococcus aureus. The expression of MpToll6-1 and MpToll7 significantly increased after infection with E. coli, whereas the expression of MpToll, MpToll6, MpToll6-1, and MpTollo continuously increased after infection with S. aureus. RNA interference-mediated suppressed expression of these genes resulted in a significant increase in the mortality of M. persicae after infection with the two bacterial species compared with that in the control group. These results suggest that MpToll genes play vital roles in the defense response of M. persicae against bacteria.